Inactivation of S-adenosyl-L-homocysteine hydrolase by cAMP results from dissociation of enzyme-bound NAD+. - Hohman, R J (1985)
S-Adenosyl-L-homocysteine hydrolase (EC 3.3.1.1) is inactivated by cAMP and also by 2'-deoxyadenosine, and in both cases, activity is restored by incubating the inactivated enzyme with NAD+. We have previously presented evidence that, despite these similarities, inactivation by these two ligands proceeds by different mechanisms. We have now used a fluorescence technique to quantitate enzyme-bound NAD+ and NADH on S-adenosyl-L-homocysteine hydrolase from Dictyostelium discoideum, and we have confirmed that cAMP and 2'-deoxyadenosine inactivate by different mechanisms. Whereas inactivation by 2'-deoxyadenosine is due to reduction of the enzyme-bound NAD+ to NADH, incubation of S-adenosyl-L-homocysteine hydrolase with cAMP results in dissociation of the enzyme-bound NAD+. The dissociation is reversible, and reactivation likely occurs by restoration of the initial NAD+ content. This reversible inactivation by cAMP may be a mechanism of controlling biological methylation reactions by adjusting intracellular concentrations of S-adenosyl-L-homocysteine through action of S-adenosyl-L-homocysteine hydrolase.